2016
DOI: 10.1590/0103-8478cr20151001
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell infusion on skin wound healing of dexamethasone immunosuppressed wistar rats

Abstract: To evaluate the therapeutic contribution of MSC intravenous infusion to surgical wound healing in dexamethasone-immunosuppressed rats, thirty-five rats were randomly divided into 2 groups: in the Control Group (CG), five rats received normal saline as 0.2ml subcutaneous (SC) injections every 24 hours, for 30 consecutive days and, in the Dexamethasone Group (DG), 30 rats were given 0.2mL subcutaneous dexamethasone (0.1mg kg-1) every 24 hours, for 30 consecutive days. After 30 days, all rats underwent surgery to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…MSCs are pluripotent cells that exist in a variety of tissues (bone marrow, cord blood and cord tissue, placental tissue, etc.) [17]. MSCs have the potential for multi-directional differentiation, and a unique cytokine secretion function.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are pluripotent cells that exist in a variety of tissues (bone marrow, cord blood and cord tissue, placental tissue, etc.) [17]. MSCs have the potential for multi-directional differentiation, and a unique cytokine secretion function.…”
Section: Discussionmentioning
confidence: 99%
“…Sacrifice was performed with overdose anesthetic injections. 16 The wounded site was excised in a circular pattern, with normal tissue included in skin specimens, and then fixed in 10% buffered formalin and processed using a paraffin tissue processing machine. Tissue specimens were cut into 5 µ thick sections, mounted on glass slides, stained with hematoxylin and eosin (H&E) stain, and examined under a light microscope to evaluate histological changes during the healing process.…”
Section: Animal Sacrifice and Specimen Preparationmentioning
confidence: 99%
“…Previous studies reported the benefits of MSCs in the cases of calvarial defects, Crohn's disease, critical limb ischemia, and multiple sclerosis, as well as in enhancement of wound healing 2 . Numerous studies have reported on the efficacy of autologous and allogeneic MSCs in applications to improve the wound healing process in various wound models 2- 15 . The effectiveness of MSCs to promote wound healing has also been proven in xenogenic applications [16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%